2007
DOI: 10.1523/jneurosci.2539-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Survival of Binucleated Purkinje Neurons by Selective Damage and Aging

Abstract: Fusion of bone marrow-derived cells with adult Purkinje cells in the cerebellum gives rise to binucleated Purkinje cells. Whether fusion can be modulated by epigenetic factors and whether fused neurons are stable has remained unclear. Here, we show that in mice and rats, partial ablation of Purkinje cells and local microglial activation in the absence of structural damage to the cerebellum increase the rate of fusion. Moreover, mouse Purkinje cells once fused with bone marrow-derived cells are viable for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
3
23

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(111 citation statements)
references
References 22 publications
10
75
3
23
Order By: Relevance
“…It is important to note that PKNs remained mononucleated in our study despite intrathecal administration of bacterial lipopolysaccharide and increased microglia numbers. This is in contrast to recent findings by Johansson et al (2008) and Magrassi et al (2007), who used focal cerebellar and inflammatory injury models and found binucleated PKNs. It suggests that the presence of binucleated PKNs in irradiated bone marrow chimeras, which we confirmed in our study, cannot be explained solely on the basis of irradiation-induced inflammation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is important to note that PKNs remained mononucleated in our study despite intrathecal administration of bacterial lipopolysaccharide and increased microglia numbers. This is in contrast to recent findings by Johansson et al (2008) and Magrassi et al (2007), who used focal cerebellar and inflammatory injury models and found binucleated PKNs. It suggests that the presence of binucleated PKNs in irradiated bone marrow chimeras, which we confirmed in our study, cannot be explained solely on the basis of irradiation-induced inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…Endogenous cell fusion has been discussed in different contexts, including physiological mechanisms like spermatozoa-ovum fusion, developmental processes like the formation of placenta, bone, and muscle (Potgens et al, 2002;Horsley and Pavlath, 2004;Chen et al, 2007), but also in the context of pathological processes like virus-induced fusion (Price et al, 1988) and tumorigenesis (Bjerkvig et al, 2005). All previous studies dealing with the investigation of fusion events in adult animals have used experimental procedures such as cell transplantation after lethal irradiation, transplantation of cells from syngeneic mice, or parabiotic models to generate chimerism (Wagers et al, 2002;Massengale et al, 2005;Magrassi et al, 2007). However, although these approaches differ significantly in the way they impact the animal, none of these approaches is physiological in a strict sense and therefore limited in establishing the contribution of endogenous BMDCs to other organs.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work has reported tance of both processes in normal homeostasis and in that neurodegeneration has an important effect in procell replacement therapies for the adult CNS. moting the arrival of BMDC and their fusion with PurMoreover, despite the strong neurodegenerative envikinje cells (3,23,30,38). This difference in the results ronment in both the cerebellum and the OB of PCD mumay be the consequence of differences in the nature and tant mice, neither Purkinje cells nor mitral cells were time course of the neurodegenerative processes and in formed from the transplanted bone marrow.…”
Section: Semmentioning
confidence: 99%
“…Unexpectedly, the neurodegenerative environment had no effect on the behavior of BMDC. In contrast, and generation of Purkinje cells (23,30,38). However, very little is known about the possible plasticity mechanisms very interestingly, the contribution of BMDC occurred through two different plasticity mechanisms, depending for other neuronal types.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative explanations that might posit the generation of stable mouse-rat heterokaryons after cell fusion as described for PCs after bone marrow grafting (18,19), are unlikely because EGFPlabeled PCs maintained mouse morphometric traits, were uninucleated (Fig. S1), and showed appropriate developmental stages in rats killed a few days after grafting (Fig.…”
Section: Discussionmentioning
confidence: 99%